Facile intra- and intermolecular charge transfer control for efficient mechanofluorochromic material. Issue 16 (29th June 2021) - Kim, Min-Ji; Ahn, Mina; Wee, Kyung-Ryang
Abstract : The mechanofluorochromism is related to the optical properties according to the electron push–pull substituent effect. As the intramolecular charge transfer decreases, strong intermolecular interactions occur, leading to mechanofluorochromism. Abstract : A series of donor–acceptor–donor (D–A–D) pyrene (Py) 2, 7-position-based compounds (CN, F, H, Me, and OMe ) were designed and synthesized to demonstrate facile intra- and intermolecular charge transfer control by an electron push–pull effect for an efficient mechanofluorochromic (MFC) material. An examination of the photophysical properties of CN–OMe revealed that the locally excited (LE) and intramolecular charge transfer (ICT) state of the compounds were modulated finely by the electron push–pull substituent effect. In addition, it is noteworthy that the CN emission originated only from the LE state despite the D–A–D molecular system. Moreover, we confirmed that the selective LE and/or ICT state modulation affects intra- and intermolecular charge transfer control in the solid-state emission. In particular, this intra- and intermolecular charge transfer control is directly dominated by MFC phenomena, which means that the molecular electron push–pull substituent effect is dependent on MFC behavior. As a result, this study shows that as the electron-withdrawing group ability increases, the intramolecular interactions become insufficient and induce strong intermolecular D–A interactions for stabilizing molecules, leading to high MFC efficiency that is reversibly repeated several times.